The Use of Cartoon Media for Junior High Students of Their Writing Ability - s. siswandi (Indonesian Journal of Integrated English Language Teaching, 2020)
This research was proposed from the problem of students writing ability in the descriptive text of the eight-grade students at MTs N 1 Pekanbaru. They were not able to write in English well. The objective of this research was to find out whether there was or nor the significant effect of using cartoon media. The design of this research was Quasi-Experimental Research. The Population of this research was all of the eighth-grade students. The total number of the population was 350 students. The writer used a cluster sampling technique by taking only two classes as a sample; VIII.1 that consisted of 35 students as experimental class and VIII.2 consisted of 35 students as control class. So the number of samples from two classes was 70 students. To analyze the data, the writer used an independent sample t-test. Based on the analysis of the t-test Formula, the sig. value is 0.000. It could be stated that 0.000<0.05. Then, the effect size is 0.387 categorized into a moderate level. The writer concluded that there is a significant effect of using cartoon media on students’ writing ability in the descriptive text at MTs N 1 Pekanbaru. And the biggest effect occurred on the writing ability where the effect size is 0.14 categorized into large effect.